Measuring dopaminergic function in the 6-OHDA-lesioned rat: a comparison of PET and microdialysis - Walker, Matthew D (Springer, 2013)
BACKGROUND: [(18) F]fluorodopa (FDOPA) positron emission tomography (PET) allows assessment of levodopa (LDOPA) metabolism and is widely used to study Parkinson's disease. We examined how [(18) F]FDOPA PET-derived kinetic parameters relate the dopamine (DA) and DA metabolite content of extracellular fluid measured by microdialysis to aid in the interpretation of data from both techniques. METHODS: [(18) F]FDOPA PET imaging and microdialysis measurements were performed in unilaterally 6-hydroxydopamine-lesioned rats (n = 8) and normal control rats (n = 3). Microdialysis testing included baseline measurements and measurements following acute administration of LDOPA. PET imaging was also performed using [(11)C]dihydrotetrabenazine (DTBZ), which is a ligand for the vesicular monoamine transporter marker and allowed assessment of denervation severity. RESULTS: The different methods provided highly correlated data. Lesioned rats had reduced DA metabolite concentrations ipsilateral to the lesion (p < 0.05 compared to controls), with the concentration being correlated with FDOPA's effective distribution volume ratio (EDVR; r = 0.86, p < 0.01) and DTBZ's binding potential (BP(ND); r = 0.89, p < 0.01). The DA metabolite concentration in the contralateral striatum of severely (>80%) lesioned rats was lower (p < 0.05) than that of less severely lesioned rats (<80%) and was correlated with the ipsilateral PET measures (r = 0.89, p < 0.01 for BP(ND)) but not with the contralateral PET measures. EDVR and BP(ND) in the contralateral striatum were not different from controls and were not correlated with the denervation severity. CONCLUSIONS: The demonstrated strong correlations between the PET and microdialysis measures can aid in the interpretation of [(18) F]FDOPA-derived kinetic parameters and help compare results from different studies. The contralateral striatum was affected by the lesioning and so cannot always serve as an unaffected control.